2012
DOI: 10.1111/j.1600-0412.2012.01415.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical‐pathologic risk factors of pelvic lymph node metastasis in stage Ib1‐IIb cervical cancer

Abstract: High LNM risk is expected in tumors of IIa stage or higher and in moderately differentiated tumors. Skip metastasis and common iliac LNM are relatively common and therefore should not be neglected. Our results suggest that standardized and complete pelvic lymph node dissection under surgery is an important measure to ensure a therapeutic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…It has long been known that histological type and grade of a tumour is indicative of metastatic risk. 18,19 A breast cancer series of >2,000 patients from 8 German centres showed that metastases at presentation were more commonly associated with grade 3 lobular histology and a Luminal B phenotype (HER2 positive). 20 In primary soft-tissue sarcoma, where histological type varies widely, tumour grade has been shown to be independent of histological subtype for predicting metastatic relapse.…”
Section: Metastatic Risk Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…It has long been known that histological type and grade of a tumour is indicative of metastatic risk. 18,19 A breast cancer series of >2,000 patients from 8 German centres showed that metastases at presentation were more commonly associated with grade 3 lobular histology and a Luminal B phenotype (HER2 positive). 20 In primary soft-tissue sarcoma, where histological type varies widely, tumour grade has been shown to be independent of histological subtype for predicting metastatic relapse.…”
Section: Metastatic Risk Assessmentmentioning
confidence: 99%
“…33 High SUV as an independent biomarker of prognosis has been borne out in lung cancer (meta-analysis of 21 lung cancer studies had a combined hazard ratio of 2.08), 34 in breast cancer (hazard ratio 2.39) 35 and in soft-tissue sarcoma (hazard ratio 3.75), 36 where it has been related to mitotic count. 37 In renal cell cancer, the apparent diffusion coefficient (ADC) 38 derived from diffusion-weighted MRI and SUV max from 18 FDG-PET have been shown to be statistically significant independent risk factors for high histological grade and hence of metastatic risk. 39 Heterogeneity of morphological and functional imaging features is proving of interest in predicting metastatic risk.…”
Section: Metastatic Risk Assessmentmentioning
confidence: 99%
See 3 more Smart Citations